2015
DOI: 10.1080/15384101.2015.1100777
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar repression facilitates initiation and maintenance of senescence

Abstract: Tumor cells with defective apoptosis pathways often respond to chemotherapy by entering irreversible cell cycle arrest with features of senescence. However, rare cells can bypass entry to senescence, or re-enter cell cycle from a senescent state. Deficiency in senescence induction and maintenance may contribute to treatment resistance and early relapse after therapy. Senescence involves epigenetic silencing of cell cycle genes and reduced rRNA transcription. We found that senescence-inducing treatments such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
(48 reference statements)
0
23
0
1
Order By: Relevance
“…Supporting our current results, several recent studies have also pointed to a crucial role of Sirt1 in orchestrating nucleolar events (Voit, Seiler, & Grummt, ). In particular, it has been shown that Sirt1 can interact (maybe indirectly) with another nucleolar protein, nucleomethylin, and formation of this protein complex is involved in modulating ribosomal biogenesis and cellular senescence in response to changes in energy supply (Murayama et al, ; Yang et al, ; Yang, Song, Chen, Soliman, & Chen, ). To our knowledge, our study is the first which reports that Sirt1 is implicated in regulating NSR.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our current results, several recent studies have also pointed to a crucial role of Sirt1 in orchestrating nucleolar events (Voit, Seiler, & Grummt, ). In particular, it has been shown that Sirt1 can interact (maybe indirectly) with another nucleolar protein, nucleomethylin, and formation of this protein complex is involved in modulating ribosomal biogenesis and cellular senescence in response to changes in energy supply (Murayama et al, ; Yang et al, ; Yang, Song, Chen, Soliman, & Chen, ). To our knowledge, our study is the first which reports that Sirt1 is implicated in regulating NSR.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, we found also BAZ2A(TIP5) among the handful of chromatin regulator genes that show elevated expression level in senescence. The Tip5 protein is thought to be involved in silencing and constitutive heterochromatin formation at rDNA, centromeres and telomeres (Guetg et al 2010;Postepska-Igielska et al 2013), and it has been recently reported that depletion of Tip5 promotes escape from senescence (Yang et al 2015b). This suggests a role for Tip5 in the regulation of a subset of H3K9me3-marked chromatin domains in senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation is the fact that MDA-MB-231 cells have significant proliferative and metastatic potential [65], poor responsiveness to anti-growth chemotherapy [66] and reduced susceptibility to autophagy [67]. Moreover, reversal of senescence occurs more often in cells like MDA-MB-231 as they are incapable of repressing rRNA transcription [68] due to reduced expression of the JmjC domain-containing histone demethylase 1B (JHDM1B) [69].…”
Section: Discussionmentioning
confidence: 83%